Molecular systematics of the subgenus Gephyromantis (Phylacomantis) with description of a new subspecies - Scherz, Mark D.; Rudolph, Janina; Rakotondratsima, Marius; Ratsoavina, Fanomezana M.; Crottini, Angelica; Andreone, Franco; Glaw, Frank; Vences, Miguel (Zootaxa, 2024)
The mantellid subgenus Phylacomantis (genus Gephyromantis) currently contains four species of frogs distributed in the South (G. corvus, G. kintana), West (G. atsingy), North East, North, and Sambirano regions (G. pseudoasper) in Madagascar. We assess the molecular systematics of these amphibians based on extended sampling and analysis of multiple nuclear-encoded and mitochondrial genes. We confirm the delimitation of the four known species, which form monophyletic groups in a mitochondrial tree and separate phylogroups without haplotype sharing in haplotype networks of four nuclear markers. Newly included samples of G. pseudoasper from the North and North East regions confirm a comparatively low genetic variation of this species across its range, with pairwise genetic distance in the 16S gene not exceeding 1.4%. On the contrary, newly collected specimens from three sites in the North East and North West of the island strongly differed from all other Phylacomantis, with genetic distances exceeding 4.8% for the16S gene. Mitochondrial and nuclear markers strongly suggest them to be sister to G. corvus from the South. Due to haplotype sharing in two nuclear genes, absence of detectable morphological differences, and lack of data on bioacoustic differentiation, we describe these populations as a new subspecies, G. corvus bakilana ssp. nov., emphasizing that this taxon may be elevated to species status in the future pending new data. This biogeographic pattern, with apparently disjunct sister lineages in the South vs. North West of Madagascar, is rare among Malagasy anurans and calls for increased exploration of the remaining humid forest fragments in the North West and West of the island.